Microbial ecology of a shallow alkaline hydrothermal vent: Strýtan Hydrothermal Field, Eyjafördur, northern Iceland - Twing, Katrina I.; Ward, L. M.; Kane, Zachary K.; Sanders, Alexa; Price, Roy Edward; Pendleton, H. Lizethe; Giovannelli, Donato; Brazelton, William J.; McGlynn, Shawn E. (Frontiers in Microbiology, 2022)
Strýtan Hydrothermal Field (SHF) is a submarine system located in Eyjafördur in northern Iceland composed of two main vents: Big Strýtan and Arnarnesstrýtan. The vents are shallow, ranging from 16-70 m water depth, and vent high pH (up to 10.2), moderate temperature (Tmax ~70°C), anoxic, fresh fluids elevated in dissolved silica, with slightly elevated concentrations of hydrogen and methane. In contrast to other alkaline hydrothermal vents, SHF is unique because it is hosted in basalt and therefore the high pH is not created by serpentinization. While previous studies have assessed the geology and geochemistry of this site, the microbial diversity of SHF has not been explored in detail. Here we present a microbial diversity survey of the actively venting fluids and chimneys from Big Strýtan and Arnarnesstrýtan, using 16S rRNA gene amplicon sequencing. Community members from the vent fluids are mostly aerobic heterotrophic bacteria, however within the chimneys oxic, low oxygen, and anoxic habitats could be distinguished, where taxa putatively capable of acetogenesis, sulfur-cycling, and hydrogen metabolism were observed. Very few archaea were observed in the samples. The inhabitants of SHF are more similar to terrestrial hot spring samples than other marine sites. It has been hypothesized that life on Earth (and elsewhere in the solar system) could have originated in an alkaline hydrothermal system, however all other studied alkaline submarine hydrothermal systems to date are fueled by serpentinization. SHF adds to our understandings of hydrothermal vents in relationship to microbial diversity, evolution, and possibly the origin of life.